Evaluation of the polymer theory applicability in describing sorption of 1,2-dichlorobenzene onto a peat soil and model sorbents - Wahid, Samsuri A., author; Doxtader, Kenneth G., advisor; Soltanpour, P. N. committee member; Tessari, John, committee member; Heil, Dean, committee member (Colorado State University. Libraries, 1999)
Sorption of hydrophobic organic compounds (HOCs) onto soil organic matter (OM) has been regarded as a partitioning process. Partitioning is characterized as having linear sorption isotherms, noncompetitive sorption, and no desorption hysterisis. However, many studies of HOC sorption onto soil OM have yielded results that are inconsistent with partitioning theory. An alternative that has received much attention is the "glassy versus rubbery polymer" theory. According to the polymer theory, sorption occurs at two distinct regions of the soil OM, amorphous and condensed regions. The amorphous region is analogous to a rubbery polymer, and the condensed region is analogous to a glassy polymer. Diffusion of HOCs into the amorphous region is fast; with linear sorption isotherms and noncompetitive sorption. On the other hand, diffusion of HOCs onto the condensed region is slow with linear sorption isotherms and competitive sorption. The present study was conducted to evaluate the applicability of this theory in describing 1,2-dichlorobenzene (DCB) sorption onto a Pahokee peat soil as well as two model sorbents, cellulose and poly-vinyl chloride (PVC). Results with these two sorbents were used to gain insight into the mechanism of DCB sorption onto soil OM. Cellulose (a rubbery polymer) was selected to model the amorphous regions and PVC (a glassy polymer) to model the condensed regions. The Freundlich model was used to fit the sorption data, and Freundlich constants (Kf) and n coefficients of the sorption isotherms were compared. Experiments were designed to measure DCB sorption and desorption with respect to (1) equilibration time; (2) effect of naphthalene as a possible competitor for sorption sites; (3) effect of naphthalene equilibration time on its competition for sorption; and (4) effect of ionic strength. The polymer theory could not adequately describe the sorption and desorption of DCB with the peat soil. The sorption isotherms were highly linear, but they were unaffected by equilibration time, which is inconsistent with the polymer theory. Except at an initial DCB concentration of 5 μg/mL, desorption of DCB from the peat soil did not vary significantly with equilibration time and initial DCB concentration, which could not be explained by the polymer theory. Pre-equilibration of the peat soil with naphthalene significantly increased DCB sorption, which is also not accounted for by the polymer theory. The lack of effect of ionic strength on DCB sorption by the peat soil suggests that diffusion, as proposed by the polymer theory, was not the dominant mechanism for the sorption process. However, the polymer theory was successful in predicting the effect of naphthalene equilibration time on naphthalene competition with DCB for sorption sites. The polymer theory was unable to describe DCB sorption with cellulose as the sorption isotherms were concentration dependent and affected by equilibration time. The polymer theory was also unable to explain desorption of DCB from cellulose as affected by equilibration time and initial DCB concentration, the increase in DCB sorption by cellulose pre-equilibrated with naphthalene, and the effect of naphthalene equilibration time on DCB sorption. The polymer theory was most successful in describing sorption and desorption of DCB with PVC. As predicted by the theory, DCB sorption onto PVC was nonlinear and time-dependent. The theory was also able to explain the effect of naphthalene equilibration time on its competition with DCB for sorption sites. Both partitioning and diffusion mechanisms appear to have been important in HOC sorption onto Pahokee peat. The high linearity of sorption isotherms for DCB with Pahokee peat is consistent with the partitioning, which is also supported by the nonlinear sorption isotherms for DCB with cellulose. The diffusion mechanism of the polymer theory would explain the reduction in DCB sorption with longer naphthalene equilibration time.
Keywords: soil sciences; environmental science